2013
DOI: 10.1093/eurheartj/eht456
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral venous congestion causes inflammation, neurohormonal, and endothelial cell activation

Abstract: Peripheral venous congestion causes release of inflammatory mediators, neurohormones, and activation of ECs. Overall, venous congestion mimicked, notable aspects of the phenotype typical of advanced and of acute HF and RF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 42 publications
2
85
0
2
Order By: Relevance
“…Therefore, it is likely that within the chronically inflamed epipharyngeal architecture, blood vessels lose their flow, forming intricate venous plexus. The resulting dysfunction of endothelial cells lining congested vessels might promote the production of inflammatory cytokines [12]. Moreover, various endothelial inflammatory mediators, such as prostanoids, histamine or nitric oxide, have all been shown to affect lymphatic drainage [13].…”
Section: Putative Mechanisms Of Eatmentioning
confidence: 99%
“…Therefore, it is likely that within the chronically inflamed epipharyngeal architecture, blood vessels lose their flow, forming intricate venous plexus. The resulting dysfunction of endothelial cells lining congested vessels might promote the production of inflammatory cytokines [12]. Moreover, various endothelial inflammatory mediators, such as prostanoids, histamine or nitric oxide, have all been shown to affect lymphatic drainage [13].…”
Section: Putative Mechanisms Of Eatmentioning
confidence: 99%
“…In vitro evidence indicates that the endothelium may become activated and turn into a primary source of pro-inflammatory, vasoconstrictive, and pro-thrombotic mediators in response to biomechanical stress [1][2][3]. Endothelial cell activation is involved in various pathogenesis of various diseases, such as heart failure and renal failure [4][5][6].…”
Section: Expression Changes Of Long Noncoding Rna In the Process Of Ementioning
confidence: 99%
“…Colombo PC developed an experimental model of acute, peripheral venous congestion in healthy human subjects and found endothelial cells were activated [3]. With microarray technology, they investigated gene expression of endothelial cells before and after venous congestion.…”
Section: Expression Changes Of Long Noncoding Rna In the Process Of Ementioning
confidence: 99%
“…It also prevents dilution of activated clotting factors, retards the inflow of clotting factor inhibitors and permits the buildup of thrombi, thereby promoting endothelial cell activation, resulting in local thrombosis and leukocyte adhesion. A recent study has shown that there is a significant increase in plasma interleukin-6 (IL-6), endothelin-1 (ET-1) and Angiotensin II (ATII) in acute peripheral venous congestion [35]. The endothelial-lined bicuspid valves in the venous system are also exposed to disturbed blood flow and reduced shear stress during the normal valve cycle [36].…”
Section: Is the Management Of Stasis Standing Still?mentioning
confidence: 99%